Transcriptional Regulation of the Peripheral Pathway for the Anaerobic Catabolism of Toluene and m-Xylene in Azoarcus sp. CIB - Blázquez, Blas (Front Microbiol, 2018)
Alkylbenzenes, such as toluene and m-xylene, are an important class of contaminant hydrocarbons that are widespread and tend to accumulate in subsurface anoxic environments. The peripheral pathway for the anaerobic oxidation of toluene in bacteria consists of an initial activation catalyzed by a benzylsuccinate synthase (encoded by bss genes), and a subsequent modified β-oxidation of benzylsuccinate to benzoyl-CoA and succinyl-CoA (encoded by bbs genes). We have shown here that the bss and bbs genes, which are located within an integrative and conjugative element, are essential for anaerobic degradation of toluene but also for m-xylene oxidation in the denitrifying beta-proteobacterium Azoarcus sp. CIB. New insights into the transcriptional organization and regulation of a complete gene cluster for anaerobic catabolism of toluene/m-xylene in a single bacterial strain are presented. The bss and bbs genes are transcriptionally coupled into two large convergent catabolic operons driven by the PbssD and PbbsA promoters, respectively, whose expression is inducible when cells grow anaerobically in toluene or m-xylene. An adjacent tdiSR operon driven by the PtdiS promoter encodes a putative two-component regulatory system. TdiR behaves as a transcriptional activator of the PbssD, PbbsA, and PtdiS promoters, being benzylsuccinate/(3-methyl)benzylsuccinate, rather than toluene/m-xylene, the inducers that may trigger the TdiS-mediated activation of TdiR. In addition to the TdiSR-based specific control, the expression of the bss and bbs genes in Azoarcus sp. CIB is under an overimposed regulation that depends on certain environmental factors, such as the presence/absence of oxygen or the availability of preferred carbon sources (catabolite repression). This work paves the way for future strategies toward the reliable assessment of microbial activity in toluene/m-xylene contaminated environments.